Understanding Consumer Purchasing Decisions Through Word of Mouth: Evidence from Somethinc Users in Malang - Helena Lovelya Purwanto (IJBAMS: International Journal of Business Accounting Management Social Science, 2026)
The rapid growth of the skincare industry in Indonesia has encouraged local brands to utilize Word of Mouth (WOM) and electronic Word of Mouth (e-WOM) as marketing communication strategies. This study aims to understand the role of WOM in shaping purchasing decisions of Somethinc consumers in Malang. This study employed a qualitative descriptive approach involving 12 informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and analyzed using interactive analysis techniques consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that WOM and e-WOM significantly influence consumer perceptions, trust, purchase intentions, and purchasing decisions toward Somethinc products. Recommendations from friends, family, beauty influencers, and digital reviews on social media platforms such as TikTok and Instagram were found to strengthen consumer confidence regarding product quality and suitability. Positive consumer experiences also encouraged repeat purchases and sustainable WOM communication among consumers. This study contributes to consumer behavior and digital marketing literature by providing a deeper qualitative understanding of the role of WOM and e-WOM in skincare purchasing decisions.